Ten reasons why A1C should not be used as a screening tool for T2DM - Shahar, Mohammad Arif (2017)
Screening of a disease can be understood as detecting a disease in an individual before clinical symptoms are apparent. In case of diabetes mellitus, as of now, the preferred screening test is still fasting blood sugar (FBS). Glycated hemoglobin (A1C) however, did make its way into guidelines as a diagnostic tool apart from its usual monitoring role. A1C is use for diagnosis rather than screening. A1C is an “index” measurement of non-enzymatic glycated hemoglobin against hemoglobin level. Therefore, there are conditions in which A1C can be falsely elevated or reduced. In patients with chronic kidney disease, carbamylated hemoglobin interferes with the assay and cause falsely elevated A1C. Conditions in which the life span of red blood cells is shortened, A1C readings are falsely lowered. In iron deficiency anemia, which is a common condition in developing countries, A1C is falsely elevated. However in those who are taking iron supplement, A1C is falsely lowered. In fact, the biology of A1C in non-diabetic individuals varies. In term of performance as a screening tool for diabetes, A1C only agrees with fasting blood sugar (FBS) about 25% of the time, and with oral glucose tolerance test (OGTT) 33% of the time. A study had shown that A1C misses 60% of diabetes cases diagnosed with OGTT. Finally, different cut-off point of A1C gives different sensitivity and specificity, whereby higher A1C improves specificity and lower improves sensitivity. One study found HbA1c of ≥ 6.5% had a sensitivity and specificity of 44% and 79%, respectively. Even guidelines could not agree on a single cut-off value for the diagnosis of type 2 diabetes mellitus. The American Diabetic Association uses an A1C cut-off value of 6.5% while the recent Malaysian Clinical Practice Guidelines on the Management of Type 2 Diabetes Mellitus uses 6.3% for diagnosis. Lastly, although a study in the UK demonstrated that screening using A1C is more cost-effective than FBS in Leicester Ethnic Atherosclerosis and Diabetes Risk (LEADER) cohort, generalization should not be made for our population, given the differences in prevalence of diabetes, age group, cut-off value of A1C, the cost and availability of the test locally.